2020
DOI: 10.1016/j.heliyon.2020.e05255
|View full text |Cite
|
Sign up to set email alerts
|

Application of biochar and inorganic phosphorus fertilizer influenced rhizosphere soil characteristics, nodule formation and phytoconstituents of cowpea grown on tropical soil

Abstract: The effect of biochar alone or co-applied with triple superphosphate on rhizosphere soil characteristics, nodule formation, phytoconstituents and antioxidant property of cowpea ( Vigna uguiculata ) is yet to be adequately examined in sub Saharan Africa. A field experiment was conducted where cowpea ( Vigna unguiculata ) was grown in a tropical sandy loam soil amended with biochar at 1.5 t ha −1 and 2.5 t ha −1 solely or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 64 publications
(77 reference statements)
4
15
0
Order By: Relevance
“…The current study results agree with the recent reports by Phares et al. (2020) and Ostadi et al. (2020).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The current study results agree with the recent reports by Phares et al. (2020) and Ostadi et al. (2020).…”
Section: Discussionsupporting
confidence: 94%
“…The current study results agree with the recent reports by Phares et al (2020) and Ostadi et al (2020). Phenolic acids such as cinnamic, carnosic, and rosmarinic acids contribute to thyme extracts antioxidant capacity (Jabri Karoui et al, 2016;Roby et al, 2013;Zengin et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The increase in pharmacologically active compounds in biochar treatments compared to control is consistent with the earlier studies that reported enhanced phenolic and flavonoid production in plants after biochar amendment in soil (Phares et al, 2020; Quartacci et al, 2017). The decrease in essential nutrient metal and photosynthetic parameters (CO 2 exchange rate, transpiration rate, and stomatal conductance) be the reason for the increased pharmacologically active compounds in plants treated with biochar (Jain et al, 2017; Saha et al, 2019; Yadav et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Regardless of the enormous benefit derived from biochar, its sole addition to soil to enhance fertility and crop yield has limitations; particularly plant based biochar. Often, plant based biochar is deficient in nitrogen ( Phares et al., 2020 ) as well as phosphorus ( Zhang et al., 2016 ). It must therefore be co-applied with compost, manure or inorganic fertilizer ( Adekiya et al., 2019 ; Phares et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%